Enhancing Beauty Education through Augmented Reality: A Case Study of Western Bridal Makeup - Lusiana, Mitra; Vici Syahril Chairani; Rizkayeni Marta (Universitas Pendidikan Ganesha, 2025)
Society 5.0 and the Fourth Industrial Revolution have driven the integration of digital technology in education, including in the field of makeup and beauty. However, skill-based learning such as Western Bridal Makeup (WBM) faces challenges due to resource limitations, such as access to quality makeup tools, accessories, and bridal gowns, hindering comprehensive mastery of makeup techniques and industry professional standards. Traditional teaching methods are considered inadequate in facilitating creativity and the hands-on learning preferences required for WBM practice. This study involved 40 students as subjects and developed an Augmented Reality (AR)-based learning media for WBM using the Research & Development method and the Multimedia Development Life Cycle (MDLC) model. The AR media simulated makeup tools, bridal gowns, accessories, tutorial videos, and flipbook modules in an interactive 3D format. The AR media provided clear representations to help students learn Western bridal makeup techniques more effectively. Data were collected through validated tests and questionnaires. The results showed a media validation score of 94.8%, with a significant impact on improving student performance (Sig. 0.000 < 0.05). Post-test scores increased significantly from 68.60 to 87.30, reflecting an improvement of approximately 20%. Students also reported better conceptual understanding and increased learning motivation. This AR media not only addresses resource limitations but also enhances student engagement, fosters creativity, and prepares them with industry-standard skills, making it an innovative solution in vocational makeup education.